2013 IEEE International Symposium on Circuits and Systems (ISCAS2013) 2013
DOI: 10.1109/iscas.2013.6572294
|View full text |Cite
|
Sign up to set email alerts
|

Self-checking ripple-carry adder with Ambipolar Silicon NanoWire FET

Abstract: Abstract-For the rapid adoption of new and aggressive technologies such as ambipolar Silicon NanoWire (SiNW), addressing fault-tolerance is necessary. Traditionally, transient fault detection implies large hardware overhead or performance decrease compared to permanent fault detection. In this paper, we focus on on-line testing and its application to ambipolar SiNW. We demonstrate on self-checking ripple-carry adder how ambipolar design style can help reduce the hardware overhead. When compared with equivalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…In Turkyilmaz et al [2013], a 4-transistor 3-input majority logic gate is proposed and reported here in Figure 11( b). Note that in static CMOS, the same gate has 10 devices in place of 4 [Rabaey et al 2003].…”
Section: Maj/mux-based Logicmentioning
confidence: 99%
“…In Turkyilmaz et al [2013], a 4-transistor 3-input majority logic gate is proposed and reported here in Figure 11( b). Note that in static CMOS, the same gate has 10 devices in place of 4 [Rabaey et al 2003].…”
Section: Maj/mux-based Logicmentioning
confidence: 99%
“…Specific examples for these nanotechnologies include, but are not limited to, silicon nanowire [1], [2], graphene [3], [4], resistive random-access memory [5], [6], spin-wave devices [7], [8], quantum-dot cellular automata [9], nanomagnets [10], DNA-logic [11], and many others [12]- [14]. We revisit logic synthesis in light of its enabling role in the selection of majority-based nanotechnologies.…”
Section: Introductionmentioning
confidence: 99%
“…1. Using controllable-polarity devices, it is possible to build very compact arithmetic logic gates, such as eXclusive OR (XOR) [4] and MAJority (MAJ) [15]. For instance, a 2-input XOR gate requires only 4 transistors [4] instead of the 8 required by the traditional full-swing static CMOS implementation [16].…”
Section: Introductionmentioning
confidence: 99%
“…We will see, in the following, that this introduces a degree of redundancy at the gate level, that is beneficial from a robustness perspective. A selfchecking ripple-carry adder architecture, exploiting this adder structure, is proposed in [15]. This architecture is far less expensive in terms of area than comparable CMOS architectures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation